Nursing of a patient with ischemic stroke combined with constipation of Qi-deficiency type and melanosis coli treated by acupoint massage (经穴推拿治疗1例缺血性中风合并气虚便秘及结肠黑变病患者的护理体会) - WANG Xuesong (王雪送); HU Shirong (胡世荣); FAN Yan (范艳); YANG Yu (杨宇); LI Chenchen (李陈晨); LIU Yanna (刘燕娜); LI Mengru (李梦儒); ZHANG Shiyu (张诗语) (中西医结合护理)
To summarize nursing management for a patient with ischemic stroke combined with constipation of Qi-deficiency type and melanosis coli treated by acupoint massage. Based on the comprehensive nursing risk assessment, the two-stage acupoint massage was carried out to relieve the pain and tonify QI-deficiency of the patient. Comprehensive nursing interventions on daily living behavior, dietary and mental health were applied to improve the recovery of gastrointestinal peristalsis and relive the constipation of Qi-deficiency type. (本文总结1例缺血性中风后合并气虚便秘及结肠黑变病患者采用经穴便秘推拿的护理经验。患者入院后完善护理评估, 基于中医辨证, 采取治标解痛和治本补虚两阶段经穴推拿, 并配合生活护理、饮食调护、情志干预等中医综合护理, 有效促进患者肠蠕动, 改善患者便秘症状。)